Applications of a decomposition inX⊗λ Y - Bator, Elizabeth M.; Slavens, Dawn R. (Annali di matematica pura ed applicata, 2001)
A Schauder Decomposition inX⊗λ when Y has a Schauder Decomposition is presented. This decomposition is then used to investigate the Approximation Property. For instance, it is shown that if X has the Approximation Property and Y has a basis thenX⊗λ has the Approximation Property. We also use this to obtain results concerning operators on vector valued continuous function spaces.